2022
DOI: 10.1007/s13538-022-01102-x
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Magnetization in Silica-coated Fe3O4 Nanoparticles Revealed by Soft X-ray Magnetic Circular Dichroism

Abstract: Magnetite (Fe 3 O 4 ) nanoparticles (NPs) and SiO 2 -coated Fe 3 O 4 nanoparticles have successfully been synthesized using co-precipitation and modified Stöber methods, respectively. The samples were characterized using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, high-resolution transmission electron microscopy (HRTEM), vibrating sample magnetomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 68 publications
3
17
0
Order By: Relevance
“…09-0432 data [ 47 ]. The XRD of MHAP NPs was also analyzed, and it found that MHAP NPs retained all the peaks of hexagonal HAP NPs with an extra peak at 2θ = 30.2° and 35.5°, which corresponds to the miller index (2 2 0) and (3 1 1) of (Fe 3 O 4 ) MNPs, respectively [ 48 ]. The other extra peaks of the MNPs in MHAP NPs were not visible due to the interference of HAP NPs.…”
Section: Resultsmentioning
confidence: 99%
“…09-0432 data [ 47 ]. The XRD of MHAP NPs was also analyzed, and it found that MHAP NPs retained all the peaks of hexagonal HAP NPs with an extra peak at 2θ = 30.2° and 35.5°, which corresponds to the miller index (2 2 0) and (3 1 1) of (Fe 3 O 4 ) MNPs, respectively [ 48 ]. The other extra peaks of the MNPs in MHAP NPs were not visible due to the interference of HAP NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 2 θ values of 57.1°, 53.6°, 43.1°, 35.5° and 30.2° were attributed to the Fe 3 O 4 crystals with diffraction crystallographic surfaces of (511), (422), (400), (310) and (220), respectively. 20,21 After successful grafting of the dendritic nanoclusters, Fe 3 O 4 @SiO 2 @PAMAM exhibited broader bands located at 2 θ angles from 17° to 24°, which was attributed to the amorphous silica. XRD signals did not change significantly with Fe 3 O 4 @SiO 2 @PAMAM after performing the molecular imprinting synthesis, indicating that the process of dendrite modification and molecular imprinting synthesis did not affect the crystal structure of the magnetite core.…”
Section: Resultsmentioning
confidence: 99%
“…In this impregnated catalyst, the iron oxide support existed in different forms like α- 54.0 (116), 62.5 (214), 64.0 (300), 71.9 (101), and 75.2 (217), respectively [41]. The 2theta values of γ-Fe 2 O 3 (Maghemite-JCPDS card 39-1356) showed 18.0° (111), 30.28° (220), 35.66° (311), 43.3° (400), 53.5° (422), 57.17° (511), 62.8° (440), and 71.4° (151), respectively [38,42]. In a similar way, Fe 3 O 4 (Magnetite-JCPDS card 65-3107) exhibited 2 theta values of 18.0° (111), 30.3° (220), 35.7° (311), 43.4°( 400), 53.5° (422), 57.2° (511), 62.8° (440), and 71.6° (151), respectively [39,42].…”
Section: Impregnated Pd-ni/iron Oxide Uncalcined and Calcined Iron Ox...mentioning
confidence: 99%
“…The 2theta values of γ-Fe 2 O 3 (Maghemite-JCPDS card 39-1356) showed 18.0° (111), 30.28° (220), 35.66° (311), 43.3° (400), 53.5° (422), 57.17° (511), 62.8° (440), and 71.4° (151), respectively [38,42]. In a similar way, Fe 3 O 4 (Magnetite-JCPDS card 65-3107) exhibited 2 theta values of 18.0° (111), 30.3° (220), 35.7° (311), 43.4°( 400), 53.5° (422), 57.2° (511), 62.8° (440), and 71.6° (151), respectively [39,42]. In this study, there is no drastic difference in the 2 theta values of γ-Fe [38].…”
Section: Impregnated Pd-ni/iron Oxide Uncalcined and Calcined Iron Ox...mentioning
confidence: 99%